A World History of Nineteenth-Century Archaeology : Nationalism, Colonialism, and the Past. - Diaz-Andreu, Margarita (Oxford studies in the history of archaeology., 2007)
An innovative history of archaeology during the nineteenth century, encompassing all its fields from the origins of humanity to the medieval period, and all areas of the world. The development of archaeology is placed within the framework of contemporary political events, with a particular focus upon the ideologies of nationalism and imperialism. - ;Margarita Diaz-Andreu offers an innovative history of archaeology during the nineteenth century, encompassing all its fields from the origins of humanity to the medieval period, and all areas of the world. The development of archaeology is placed w.